2022
DOI: 10.20473/jaki.v10i1.2022.31-40
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study: Hospital Patient Complaint Management

Abstract: Background: Complaint management is vital for hospitals as patient complaints can be used to advance the quality of health services provided. Aims: This study analyzed patient complaint management at an X government hospital in Yogyakarta. Methods: The research used a descriptive-qualitative method and phenomenology, which was carried out through in-depth interviews, observation, and document review. It involved the head of the legal and public relations department, the head of the public relations sub-divisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The research found that the management of hospital service complaints that are included in these public facilities has been formulated in Law Number (No). 25 of 2009 concerning Public Services, where the submission of suggestions and complaints needs to be made to improve the quality of these services [32].…”
Section: Discussionmentioning
confidence: 99%
“…The research found that the management of hospital service complaints that are included in these public facilities has been formulated in Law Number (No). 25 of 2009 concerning Public Services, where the submission of suggestions and complaints needs to be made to improve the quality of these services [32].…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, Hastuti et al (2022) underscores the importance of providing complaintreporting platforms, such as suggestion boxes.…”
Section: Regional Government Policy In the Implementation Of Child-fr...mentioning
confidence: 99%